Characterisation of an autochthonous mouse ccRCC model of immune checkpoint inhibitor therapy resistance - Asin Peighambari; Hsin Huang; Patrick Metzger; Mojca Adlesic; Kyra Zodel; Silvia Schäfer; Philipp Seidel; Lukas M. Braun; Jan Hülsdünker; Wolfgang Melchinger; Marie Follo; Manching Ku; et al. (Scientific Reports)
Abstract Many metastatic clear cell renal cell carcinomas (ccRCC) are resistant to immune checkpoint inhibitor therapies, however the mechanisms underlying sensitivity or resistance remain incompletely characterised. We demonstrate that ccRCCs in the Vhl/Trp53/Rb1 mutant mouse model are resistant to combined anti-PD-1/anti-CTLA-4 therapy alone and in combination with additional therapeutic agents that reflect current ccRCC clinical trials. However, in some animals in vivo checkpoint therapy allowed isolated splenic T cells to recognise cultured ccRCC cells from the same animal, implicating the tumour microenvironment in suppression of T cell activation. We identified putative immunosuppressive myeloid cell populations with features similar to myeloid cells in the microenvironment of human ccRCC. The expression patterns of immune checkpoint ligands in both the mouse model and in human ccRCC suggests that several checkpoint systems other than PD-1 and CTLA-4 are likely to represent the dominant T cell suppressive forces in ccRCC. Our findings characterise an autochthonous mouse ccRCC model of immune checkpoint inhibitor therapy resistance and pave the way for a systematic functional dissection of the identified potential molecular barriers to effective immune therapy of ccRCC.